Online Training Application Design with Website-Based Blended Learning System Method - Magalhaes, Augusta De Jesus; Sopwandin, Iwan; Bakri, Asri Ady (Yayasan Gema Bina Nusantara, 2023)
The Ministry of Health provides training to employees to improve their skills and level of service to the people of Indonesia. In the health service training activities carried out, employee training is carried out through seminars. The seminar was conducted in the form of application presentations and hardcopy manuals. The implementation that has been implemented is still lacking because there is no online application that helps the facilitator measure participants' understanding. Therefore, the researchers built an application that aims to produce a website-based online training application. The system development method uses Rapid Application Development (RAD), which is modeled using Unified Modeling Language (UML) tools. Using the PHP programming language and MySQL as a Relational Database Management system, this research produces a training application that can assist the Ministry of Health, especially the Center for Data and Information, in conducting training.